The Social Representations: Theory, Evolution and Applicability: A View from Praxeology - Caraballo-Noriega, Natalia; Prieto-Flórez, Javier (EFIM Ediciones, 2018)
The purpose of this article is to review the theory of social representations, various authors who have developed the topic, its evolution and applicability in different areas of knowledge. An approach to this theory is made through a bibliographic search in platforms such as WOS (Web of Science) and Scopus, decanting by themes, authors and year of publication, this as an attempt to locate a dissemination scenario for this theory. Finally, con-clusions about the general perspective of the review and the state of development are made.